2019
DOI: 10.1186/s12937-019-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in relation to testosterone levels and severity of impaired kidney function among middle-aged and elderly men in Taiwan: a cross-sectional study

Abstract: Background Chronic Kidney Disease (CKD), characterized by an impaired kidney function, is associated with low testosterone levels. This study investigated the association between dietary patterns, testosterone levels, and severity of impaired kidney function among middle-aged and elderly men. Methods This cross-sectional study used the database from a private health-screening institute in Taiwan between 2008 and 2010. Men aged 40 years old and older ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In a similar sample, we also found that nuts or legumes intake had no associations with the self‐reported EF. In our study, the results of MVA on the association between testosterone levels and the diet were in line with several prior studies (Kuchakulla et al., 2020; Kurniawan et al., 2019). Therefore, it can be believed that the plant‐based diet has no relationship with testosterone levels.…”
Section: Discussionsupporting
confidence: 93%
“…In a similar sample, we also found that nuts or legumes intake had no associations with the self‐reported EF. In our study, the results of MVA on the association between testosterone levels and the diet were in line with several prior studies (Kuchakulla et al., 2020; Kurniawan et al., 2019). Therefore, it can be believed that the plant‐based diet has no relationship with testosterone levels.…”
Section: Discussionsupporting
confidence: 93%
“…Three dietary patterns were identified using principal component analysis, and food items were retained in the pattern if the absolute cut-off value of a factor loading was ≥0.30 (Supplementary Table S1). Dietary pattern scores were calculated for each pattern by summing up the frequency of food items weighted by their factor loadings [33].…”
Section: Other Covariatesmentioning
confidence: 99%
“…To our knowledge, most of the current studies investigating the association of dietary patterns with kidney disease in healthy individuals or populations with diabetes have explored the effects of diet on indicators related to renal function. [14][15][16] However, few studies have explored the relationships between dietary patterns and renal impairment in populations of individuals with diabetes. Consequently, this study investigated the associations of dietary patterns with renal impairment in adult patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%